The Lord Peter Wimsey mysteries. Set one [videorecording (DVD)] - David, Hugh; Wilson, Ronald; Carmichael, Ian, 1920-2010; Sayers, Dorothy L. (Dorothy Leigh), 1893-1957 (Sayers, Dorothy L. (Dorothy Leigh), 1893-1957. Lord Peter Wimsey mystery., 2009)
Clouds of Witness - Death hits close to home when Lord Peter's future brother-in-law is murdered. Complicating matters is the man who stands accused: Gerald Wimsey, Lord Peter's brother. The Unpleasantness at the Bellona Club - When a member of the prominent Bellona Club dies on the same day as his sister, Lord Peter must determine who will inherit a sizeable fortune. Bonus features included.